SHANK2 mutations: synapse homeostasis in Autism Spectrum Disorders (ASD) - Oliveira, Bárbara (2011)
ASD are a heterogeneous group of neurodevelopmental disorders presenting a complex inheritance pattern. The genetic causes of ASD are diverse, but the majority of genes previously implicated participate in the development and function of neuronal circuits. Mutations in genes encoding synaptic cell adhesion molecules and scaffolding proteins, such as neuroligins (NLGN), neurexins (NRXN) and the SHANK family, have been recurrently reported in patients with ASD. SHANK2 encodes a scaffolding protein located in the postsynaptic density (PSD) of glutamatergic synapses, and mutations in ProSAP1/SHANK2 have been recently associated with both ASD and intellectual disability.